Juvenile Generalized Myasthenia Gravis With AChR and MuSK Antibody Double Positivity: A Case Report With a Review of the Literature - Ge, XiuShan; Wei, CuiJie; Dong, Hui; Zhang, YueHua; Bao, XinHua; Wu, Ye; Song, DanYu; Hao, HongJun; Xiong, Hui (Frontiers in Pediatrics, 2022)
Myasthenia gravis is an autoimmune disease mediated by B cells and is associated with acetylcholine receptor (AChR) and muscle-specific receptor tyrosine kinase (MuSK) antibodies in the postsynaptic membrane at the neuromuscular junction. The presence of both antibodies in the serum of patients with myasthenia gravis has been rarely reported. Case description: A 9-year-old girl was admitted to our hospital with the chief complaints of reduced facial expression for 3 months and unclear speech and choking from drinking water for 2 months. The diagnosis of generalized myasthenia gravis was made based on clinical manifestations, repetitive electrical nerve stimulation, neostigmine tests, specific antibody tests and other auxiliary examinations. We found the rare coexistence of two key antibodies (anti-AChR and anti-MuSK antibodies) in the patient's serum. The patient experienced myasthenic crisis and received respiratory support even though she was taking prednisone therapy. Due to the poor response to treatment with pyridostigmine bromide, glucocorticoids and IVIG, we administered rituximab therapy, and she responded well and achieved clinical remission. This suggests that clinicians should pay more attention to atypical cases and antibody detection. Rituximab should be considered when conventional treatment fails.